Mineralogy, geochemistry and Sm-Nd systematics of rocks and ores of the Kanakay iron skarn deposit (Southern Urals) (Proceedings of Voronezh State University. Series: Geology, 2023)
Introduction: Iron skarn deposits are of great commercial importance, but the sources of mineralization are debatable. In recent years, this problem has been increasingly addressed by the geochemistry of major and accessory minerals, as well as isotopic geochemistry, including stable and radiogenic isotopes. Methodology: The mineral composition of rocks and ores was studied using scanning electron microscopy (Tescan Vega Compact). The chemical composition of rocks and ores was determined using an X-Calibur X-ray fluorescence spectrometer. The study of the Sm-Nd isotope system was carried out on a seven-channel mass spectrometer Finnigan-MAT 262 (RPQ). Results and discussion: For the first time, detailed studies of the mineral composition and geochemical features of rocks and ores of the Kanakay skarn-magnetite deposit (Southern Urals) were carried out. Geological, mineralogical, and geochemical data are consistent with the post-skarn hydrothermalmetasomatic origin of magnetite ores that replaced brecciated marbled limestones at contact with gabbroids of the Utlyktash complex. Pre-ore (garnet, clinopyroxene) and post-ore (chlorite, prehnite) minerals of metasomatites were studied in detail to assess the conditions of ore formation. Sm-Nd isotopic data (εNd(T) = ˗3.4...+7.2) for rocks and ores indicate heterogeneity of the mineralization source and probable intensive fluid processing of ores. Conclusion: The skarn-magnetite ores of the Kanakay deposit were deposited in the temperature range of 219–492°C, and the source of Fe could be both intrusion gabbroids and host rocks.
Keywords: skarn-magnetite ores; mineralogy; geochemistry; Sm-Nd isotopic systematics